The repetition and competition of news reporting as mediator to frame setting - Mohd Zawawi, Julia Wirza; Chang, Peng Kee; Ahmad, Fauziah (Elsevier Ltd., 2014)
The rapid spread of information in the world makes news reporting on the current issues around people grows as well.Framing analysis is a theoretical approach that has been considered as one of the indicators used to analyze how people understand the situations.With the diversity of perception, framing analysis too has changed. The competition of news reporting from various types of media gives the audiences more options to choose the frame which is considered right and suitable for them. Similarly, the media also take the initiatives by reporting a repeated news and information in order to provide information and insight to the reader as well as to capture their attention.Therefore, this study opens a new stream of framing analysis on how these two mediators are functional and capable of giving effect to the news framing.